Weathering a Cytokine Storm - Tiffany Y. Shaw MD; Michael Schivo MD (SAGE Publishing, 2016)
Hemophagocytic lymphohistiocytosis (HLH) is a rare but life-threatening disease caused by excessive immune activation. Acquired HLH is seen in adults and is often caused by infection or malignancy. Diagnosis is difficult and usually missed as clinical and laboratory findings are nonspecific. Moreover, the pathophysiology of the systemic inflammatory response syndrome and/or sepsis is remarkably similar to HLH. Thus, in patients presenting with presumed severe sepsis or septic shock complicated by multiorgan failure without a clear infectious source, HLH should be considered. A disproportionately high ferritin may be one of the earlier laboratory findings to suggest HLH. We discuss a case of a young male who presented with presumed septic shock with multiorgan failure who was eventually found to have Epstein-Barr virus-induced HLH.